2023
DOI: 10.3390/children10020242
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in Very Low Birth Weight Infants: A Major Morbidity and Mortality Risk Factor

Abstract: Background and objectives: Very low birth weight (VLBW) infants are at high risk of developing acute kidney injury (AKI), presumably secondary to low kidney reserves, stressful postnatal events, and drug exposures. Our study aimed to identify the prevalence, risk factors, and outcomes associated with AKI in VLBW infants. Study design: Records of all VLBW infants admitted to two medical campuses between January 2019 and June 2020 were retrospectively reviewed. AKI was classified using the modified KDIGO definit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 70 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…As the effect of AKI becomes clearer in critically ill neonates, 1,4,5,7,8 it is important to better understand high-risk states such as rAKI, which has been understudied. To our knowledge, this secondary analysis of the AWAKEN study is the first multicenter analysis of the incidence, risk factors, and outcomes associated with rAKI in a broad cohort of critically ill neonates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the effect of AKI becomes clearer in critically ill neonates, 1,4,5,7,8 it is important to better understand high-risk states such as rAKI, which has been understudied. To our knowledge, this secondary analysis of the AWAKEN study is the first multicenter analysis of the incidence, risk factors, and outcomes associated with rAKI in a broad cohort of critically ill neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) occurs commonly in critically ill neonates and is independently associated with adverse outcomes, including longer length of hospital stay (LOS) and increased mortality. [1][2][3][4][5][6][7][8][9][10] Acute kidney injury may predispose neonates to subsequent kidney injury, and survivors of neonatal AKI are potentially at risk for long-term complications, including chronic kidney disease. 11,12 As our understanding of the incidence and impact of neonatal AKI becomes clearer, it is important to better understand the incidence and outcomes associated with the occurrence of more than 1 episode of neonatal AKI after resolution of a previous AKI episode during the same hospitalization, or recurrent AKI (rAKI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, very-low-birth-weight babies are at an increased risk due to insufficient renal reserves, stressful postnatal events, and medication exposures [26]. Lazarovits et al reported a 21% prevalence of AKI in 152 infants with very low birth weight, with predictors including the use of vasopressors, patent ductus arteriosus, and bloodstream infection [26]. Neonatal mortality and AKI were strongly correlated [26].…”
mentioning
confidence: 99%
“…Lazarovits et al reported a 21% prevalence of AKI in 152 infants with very low birth weight, with predictors including the use of vasopressors, patent ductus arteriosus, and bloodstream infection [26]. Neonatal mortality and AKI were strongly correlated [26]. Various methods exist to diagnose AKI [9,27], such as the widely used risk, injury, failure, loss, and end-stage (RIFLE) criteria [28].…”
mentioning
confidence: 99%